A Critical Review of the Book Religion and Theory of International Relations: Theory and Practice - Bahram Navazeni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Religion and Theory of International Relations: Theory and Practice” is a collection of articles compiled and translated into Persian by Asgar Ghahramanpour Bonab from scattered articles and journals by Daniel Filpat and several other researchers of international relations. By compiling these articles, the translator has attempted to address the important role of religion in shaping international relations in the Westphalian period and by evaluating its position among various mainstream and minor theories of international relations such as realism, liberalism, and constructivism, he has explored the function of different world religions such as Christianity, Islam, Hinduism, Buddhism, and Judaism, both in inciting civil strife and converging, and in uniting and strengthening the world peace. Given the importance of familiarity with different types of religions, as well as their historical role in the formation of societies and their developments, especially in the contemporary period, this article examines and evaluates this book and tries to recommend some formal as well as content revisions on translation, equivalence, and references. The authors of the articles, as well as the translator, seem to have neglected to observe the prevailing modern situation of the separation of religion from politics and the marginalized religion in contemporary international relations.